miR-544 promotes maturity and antioxidation of stem cell-derived endothelial like cells by regulating the YY1/TET2 signalling axis - Jianming Guo; Qiuling Xiang; Yaojie Xin; Yongyi Huang; Gang Zou; Te Liu (Cell Communication and Signaling, 2020)
Abstract Background Inflammation and oxidative stress induced by oxidized low density lipoprotein are the main causes of vascular endothelial injury and atherosclerosis. Endothelial cells are important for the formation and repair of blood vessels. However, the detailed mechanism underlying the regulation of maturity and antioxidation of stem cell-derived endothelial like cells remains unclear. Besides, YY1 and TET2 play a key role on epigenetic modifications of proliferation and differentiation of stem cells. However, the regulatory mechanism of epigenetic modification induced by YY1 and TET2 on stem cells to iECICs is also not clear. Aim Here, we want to investigate detailed mechanism underlying the regulation of maturity and antioxidation of stem cell-derived iECICs by by YY1 and TET2. Methods The qPCR, Western blot, immunohistochemical staining and flow cytometric analysis were used to analyze the expression level of each gene. Luciferase reporter assay was used to detect the binding sites between microRNA and target genes. The hMeDIP-sequence, ChIP-PCR and dot blot were used to detect the 5-hydroxymethylcytosine modification of genomic DNA. ATP, ROS, SOD assay were used to evaluate of oxidative stress in cells. The iECICs transplantation group The ApoE−/− mice were intravenous injected of iECICs to evaluation of therapeutic effect in vivo. Results Our studies have found that as the differentiation of human amniotic epithelial cells (HuAECs) is directed towards iECICs in vitro, the expression levels of vascular endothelial cell markers and miR-544 increase significantly and the expression level of YinYang 1 (YY1) decreases significantly. The luciferase reporter assay suggests that Yy1 is one of the targets of miR-544. Hydroxymethylated DNA immunoprecipitation sequencing showed that compared with HuAECs, iECICs had 174 protein-coding DNA sequences with extensive hydroxymethylation modifications. Overexpression of miR-544 inhibits the activity of the YY1/PRC2 complex and promotes the transcription and expression of the ten-eleven translocation 2 (TET2) gene, thereby activating the key factors of the serotonergic synapse pathway, CACNA1F, and CYP2D6. In addition, it promotes ability of maturity, antioxidation and vascular formation in vitro. Meanwhile, transplantation for miR-544-iECICs can significantly relieve oxidative stress injury on ApoE−/− atherosclerotic mice in vivo. Conclusions miR-544 regulates the maturity and antioxidation of iECICs derived from HuAECs by regulating the YY1/TET2/serotonergic synapse signalling axis. Video abstract